Reassembling disaster risk: towards a more self-reflexive and enabling geography - Kewan Mertens (Belgeo)
Physical and human geographers tend to look at the world as something that needs to be discovered and explained. Finding bits of nature or society, they further drive a wedge between their disciplines. By means of a case study I investigate how assemblage thinking, which does not hold the separation between nature and society, may be useful to make more conscious choices about which world we want to live in. I look back at a research project on landslide risk in Equatorial Africa in which I participated from 2014 till 2018. In this project, landslide risk as a scientific concept was used to productively enact a landslide risk assemblage in the case study area. It thereby unintentionally silenced other realities and identities. I show how the productive strength of the concept partially rests on its denial of alternative possibilities. By the end of the project the landslide risk assemblage nevertheless remained fragmentary and unfinished. This observation, I argue, is encouraging since it highlights that we may always maintain some agency regarding the world we want to live in. Towards the end of the manuscript I therefore make some, rather bold, statements about the way geographers could conceive their work.